The Grim Reality of Health System Uncovered with COVID-19 Pandemic in Nepal - Nepal, Richa; Bhattarai, Bharosha (Journal of Nepal Health Research Council, 2020)
With advent of community transmission of COVID-19 in Nepal, the number of cases continues to rise and poses threat to the fragile health system of our country. ‘Trace, isolate, test and treat’ is the strategy advocated by World Health Organization to fight against COVID-19. Despite the efforts for last nine months, Nepal lacks in some aspect of this strategy. Lack of prompt testing facilities and substandard quarantine and isolation centers, have led to mismanagement of cases. The panic regarding COVID-19, lack of adequate protective measures to healthcare workers in early stage of the pandemic, and nation-wise lockdown, has led to collateral damage in the form of increased morbidity and mortality due to non-COVID related illnesses. COVID-19 pandemic has uncovered the grim reality of the debilitated health system of our country. With mass influx of Nepali migrant workers, the epidemic is expected to grow exponentially. We need to understand that the health system of Nepal must be prepared to function to its maximum capacity in the coming days. Keywords: COVID-19; health; Nepal; pandemic